Bridging monetary policy and the real sector: A conceptual model in Islamic economics - Ilma Mahdiya; Abdul Wahab; Muhammad Hasan Afdhali (Indonesian Journal of Islamic Economics Research, 2026)
The disconnect between monetary policy and the real sector remains a key issue in modern economic systems, including Islamic finance, where decoupling between financial activities and productive sectors distorts the efficiency of monetary transmission channels. Previous studies have discussed Islamic monetary instruments and financial intermediation separately, with limited attention to an integrated framework linking Islamic monetary policy, Islamic financial institutions, and the real sector within a maqasid al-Shariah perspective. This study aims to develop a conceptual model that bridges Islamic monetary policy and the real sector within an integrated framework.. The findings suggest an integrated model that links Islamic monetary instruments, Islamic financial institutions, and real sector activities through a dynamic feedback mechanism, with maqasid al-Shariah as the normative foundation. In contrast to conventional monetary frameworks relying on interest-based transmission mechanisms, the proposed framework emphasizes profit-sharing, asset-backed financing, and ethical resource allocation linked to productive activities. This study highlights the importance of strengthening Sharia-compliant monetary instruments, institutional integration, and maqasid-based policy design to support inclusive, sustainable, and real-sector-oriented economic development.